The COVID-19 Catalyst: Analysis of a Tertiary Academic Institution's Rapid Assimilation of Telemedicine. Issue 4 (20th July 2020) - Davis, Clayton; Novak, Mary; Patel, Apexa; Davis, Cordell; Fitzwater, Ryan; Hale, Nathan
Abstract: Introduction: The COVID-19 pandemic forced all urology practices to reconsider the necessity of face-to-face office encounters. Seeking to reduce patient exposure, our urologic oncology office made an immediate transition to telemedicine and this study reports our experience. Methods: Beginning March 17, 2020 the urologic oncology department committed to see all patients via telemedicine, unless they needed a cystoscopy for high grade urothelial cell carcinoma or recent gross hematuria, or required removal of a Foley catheter or surgical drain. March 17 was assigned day 1, and for the next 14 days rates of face-to-face, audio and audiovisual encounters were recorded. A telephone survey was conducted with all patients who participated in an audiovisual encounter. Results: In analyzing the numbers of face-to-face, audio and audiovisual encounters, after day 5 more patients participated in audiovisual encounters than any other modality. By day 10 no nonessential face-to-face encounter occurred. There was an 80.4% response rate to our survey. Average patient account setup time was 10.5 minutes and 35.1% required assistance from our office to set up their account, averaging 7.1 minutes. No-show rates of face-to-face encounters were significantly higher than for audiovisual encounters (face-to-face 67%, audiovisual 17%, p <0.001). Overall 82% of patients surveyed were likely to elect for a telemedicine encounter over a face-to-face encounter for a routine visit during future flu seasons. Conclusions: The current study describes the initial adoption, early clinical experience and patient impressions of rapid implementation of telemedicine during the COVID-19 pandemic.